PARTISIPASI PETERNAK SAPI DALAM PENYULUHAN DI DESA TONDEGESAN SATU KECAMATAN KAWANGKOAN KABUPATEN MINAHASA - Tulong, Vanessa J.M; Sajow, A A; Lenzun, G D; Lenzun, G D; Lombogia, S O.B (ZOOTEC, 2019)
ABSTRACTPARTICIPATION OF CATTLE FARMERS IN COUNSELING AT TONDEGESAN SATU VILLAGE KAWANGKOAN DISTRICT MINAHASA REGENCY.The participation of cattle farmers are very important in counseling activity because it can help the breeder to get the important informations about development of farms cow. The purpose of this study was to determine information about villages in Tondegesan Satu Village, Kawangkoan District, Minahasa Regency. This research was run by Miles and Huberman analysis using survey methods. espondents were selected using purposive to breeders methods that once had activities in Tondegesan Satu Village Kawangkoan District, Minahasa District amount 30 respondents and data collection was done by direct interviews with cattle farmers by the help of questionnaires. The results of this study is indicate that the participation in planning, participation in activity and participation in the utilization of results is great.Keywords : Participation, Counseling, CowFarmers